2013
DOI: 10.1093/aje/kwt019
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Body Mass Index and Body Height With Low Back Pain in 829,791 Adolescents

Abstract: Body mass index (BMI) (calculated as weight (kg)/height (m)²) and height are linked to the pathogenesis of low back pain, but evidence-based confirmation is lacking. We examined the prevalence of low back pain in adolescents and its association with BMI and height. Disability clauses (official military limitations related to a person's health status) indicating low back pain severity were divided according to symptoms of low back pain alone and symptoms of low back pain with objective corroborating findings. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
44
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(50 citation statements)
references
References 22 publications
5
44
1
Order By: Relevance
“…Some studies already demonstrated larger body height as a risk factor for future LBP (Coeuret-Pellicer et al, 2010;Hershkovich et al, 2013). This could not be confirmed by the current study since the variable height was not significant in the regression analysis.…”
Section: No Lbp -No Lbpcontrasting
confidence: 92%
“…Some studies already demonstrated larger body height as a risk factor for future LBP (Coeuret-Pellicer et al, 2010;Hershkovich et al, 2013). This could not be confirmed by the current study since the variable height was not significant in the regression analysis.…”
Section: No Lbp -No Lbpcontrasting
confidence: 92%
“…This has important consequences in both fundamental science, for example, in genome-wide association study design, and applied science, such as pharmacogenetic development of novel analgesics. Covariates such as BMI with highly significant association as observed in the present study, but also by others (e.g., Hershkovich et al, 2013), may have little practical gene-finding significance due to their modest contribution to risk of the disease manifestation.…”
Section: Discussionsupporting
confidence: 52%
“…To preserve anonymity of participants, demographic information was limited to age and Body Mass Index (BMI), which have been identified as risk factors for musculoskeletal pain in the general population [8,15,16]. The hours per week spent on five activities were used to assess lifestyle of medical students: Exercising, sleeping, studying, sitting and walking.…”
Section: Surveymentioning
confidence: 99%